# How do you write the expression #(x+6)(x-2)# as a polynomial in standard form?

##### 2 Answers

The final answer:

#### Explanation:

To write the expression

#x xx x = x^2#

#x xx (-2) = -2x#

#6 xx x = 6x#

#6 xx (-2) = -12#

After foiling completely you get:

#x^2 - 2x + 6x -12#

Next, you combine like terms.

#-2x + 6x = 4x#

There are no other like terms. Therefore, your final answer is

#x^2 + 4x - 12#

Mar 21, 2016

It's really a lot easier to see the FOIL method than explain.

Then, once foiled out, combine like terms.

Your final answer will be, x^2 +4x -12